2001
DOI: 10.1104/pp.125.2.1001
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Plant β-Ureidopropionase and Functional Overexpression in Escherichia coli

Abstract: Pyrimidine bases are rapidly catabolized in growing plant tissues. The final enzyme of the catabolic pathway, ␤-ureidopropionase (␤-UP; EC 3.5.1.6), was partially purified from the shoots of etiolated maize (Zea mays) seedlings. The enzyme had a K m for ␤-ureidopropionate (the substrate derived from uracil) of 11 m. Only one enantiomer of racemic ␤-ureidoisobutyrate (derived from thymine) was processed with a K m of 6 m. The enzyme was inactivated by dialysis against 1,10-phenanthroline and activity could be p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
51
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 30 publications
2
51
0
Order By: Relevance
“…It is synthesized by the condensation of b-alanine and pantoic acid (Genschel et al 1999). In higher plants, three possible pathways of b-alanine biosynthesis have been reported; these are the spermidine route (Terano andSuzuki 1978, Rastogi andDavies 1989), the propionate route (Hatch andStumpf 1962, Rathinasabapathi 2002) and the uracil route (Walsh et al 2001, Duhazé et al 2003. Our results strongly suggest that the uracil route, at least, contributes to pantothenic acid synthesis in potato leaves.…”
Section: Biosynthesis Of Pantothenic Acid From Uracilmentioning
confidence: 58%
“…It is synthesized by the condensation of b-alanine and pantoic acid (Genschel et al 1999). In higher plants, three possible pathways of b-alanine biosynthesis have been reported; these are the spermidine route (Terano andSuzuki 1978, Rastogi andDavies 1989), the propionate route (Hatch andStumpf 1962, Rathinasabapathi 2002) and the uracil route (Walsh et al 2001, Duhazé et al 2003. Our results strongly suggest that the uracil route, at least, contributes to pantothenic acid synthesis in potato leaves.…”
Section: Biosynthesis Of Pantothenic Acid From Uracilmentioning
confidence: 58%
“…Furthermore, kinetic studies demonstrated that rat ␤AS is an allosteric enzyme with positive cooperativity toward the substrate N-carbamyl-␤-alanine, which triggers a change in the oligomeric state from homohexamer to homododecamer, whereas the presence of the reaction product ␤-alanine induces the dissociation into inactive trimers (16). The two characterized plant ␤ASs exist as homodecamers at pH 7, with subunit molecular masses comparable with those of the mammalian enzymes (43-45 kDa) (15). In contrast, Sk␤AS is a homodimer, and kinetic studies do not support an allosteric regulation of the enzyme.…”
mentioning
confidence: 84%
“…The presence of a dimetal site in this enzyme became apparent after calculation of the initial electron density map, which showed two connected peaks of strong density. The high structural similarity of Sk␤AS to dizinc-dependent exopeptidases, the results of the metal analyses performed for other ␤ASs (14,15), and the type of ligands coordinating the metal ions suggested zinc as the most probable type of metal. After inclusion of two zinc ions/subunit in the model, the distances to the coordinating residues refined to those usually observed in zinc-binding sites.…”
Section: Metal-binding Sitementioning
confidence: 99%
See 1 more Smart Citation
“…Eukaryotic AS has been purified and characterized from a number of sources (Sanno et al, 1970;Wasternack et al, 1979;Tamaki et al, 1987;Gojković et al, 2001;Walsh et al, 2001;Waldmann et al, 2005). Their subunit molecular weights range from 42 to 50 kDa.…”
Section: Introductionmentioning
confidence: 99%